Penerapan Self Regulated Learning sebagai Upaya Meningkatkan Motivasi Belajar Siswa SMA Muhammadiyah 10 GKB - Muayadah, Faisatul (Jurnal Riset Psikologi, 2024)
Abstract. Learning motivation plays a crucial role in students' academic achievement, especially at the high school level. Many students experience a decline in learning motivation, indicated by their inability to set learning goals, lack of initiative, and frequent procrastination. This study aims to enhance students' learning motivation by applying self-regulated learning (SRL) strategies and to identify the levels of learning motivation among students at SMA Muhammadiyah 10 GKB. The research employed a quantitative method with a one-group pretest-posttest design. The participants were students with moderate learning motivation, evaluated through interviews and observations. The findings revealed that the implementation of SRL significantly increased students' learning motivation. The motivation scores improved from a moderate category (pretest scores <81.3) to a high category (post-test scores >81.3) after the intervention. The Wilcoxon test showed significant results (Asymp. Sig. 0.003), confirming the effectiveness of the intervention. The SRL technique helped students manage their time, set goals, solve problems, and evaluate learning outcomes, making them more independent and motivated. Abstrak. Motivasi belajar sangat penting bagi prestasi akademik siswa, terutama di Sekolah Menengah Atas. Banyak siswa mengalami penurunan motivasi belajar. Indikator rendahnya motivasi ini meliputi ketidakmampuan menetapkan tujuan belajar, kurangnya inisiatif , dan sering menunda tugas. Penelitian ini bertujuan untuk meningkatkan motivasi belajar Siswa dengan mnerapkan strategi self-regulated learning (SRL) serta untuk mengetahui tingkatan motivasi belajar siswa-siswi SMA Muhammadiyah 10 GKB. Metode yang digunakan adalah kuantitatif dengan desain penelitian one group pretest-postest. Subjek penelitian adalah siswa dengan motivasi belajar dalam kategori sedanh, yang dievaluasi melalui wawancara dan observasi. Hasil penelitian menunjukkan bahwa penerapan SRL secara signifikan meningatkan motivasi belajar siswa. Skor motivasi belajar meningkat dari kategori sedang (nilai pretest <81,3) menjadi kategori tinggi (nilai post-test >81,3) setelah intervensi. Uji Wilcoxon menunjukkan hasil signifikan (Asymp. Sig. 0,003), mengonfirmasi efektifitas intervensi. Teknik SRL membantu siswa dalam mengelola waktu, menetapkan tujuan, memecahakan masalah, dan mengevaluasi hasil belajar, sehingga mereka menjadi lebih mandiri dan termotivasi.